Service Quality and Leadership in the Restaurant Industry Revisited: The COVID and Great Resignation Effect - Koutroumanis, Dean A.; Dixon, Deirdre (Journal of Applied Business and Economics, 2023)
This manuscript examined the literature and posited recommendations for restaurant professionals to develop successful and sustainable training programs to improve service delivery in the post-COVID-19 era. This research adds to the literature on service quality, behavioral intentions, and servant leadership in the restaurant industry. The literature indicated that the constructs continue to play an integral role in attracting and retaining restaurant customers. The findings led to practical applications for restaurateurs with strategies to improve service delivery practices, generate more repeat customers and attract quality employees in the post-COVID-19 environment.